The reception of César Vallejo’s Colacho hermanos (1934) by literary criticism - Ventura Vásquez, Williams Nicks (2023)
The critical approaches to Peruvian theater in the twentieth century have contributed to verify the procedure of scenic representation and the way of stylistic elaboration of the dramatic composition. This approach has propitiated a sequentiality of approaches to the theatrical process related to diverse tendencies or sensibilities established in several periods. Specifically, the balance of César Vallejo’s plays evidences the commitment and exhaustive search of the famous bard to elaborate an innovative artistic composition. In this sense, the present research aims to review the perspectives of literary criticism regarding the play Colacho hermanos (1934).